The experience of using serotonin adipate in intensive care unit for non-surgical patients with gastrointestinal dysfunction - Nikolai P. Krotenko; Marina S. Grinenko (LLC "MEDIAFORMAT", 2023)
Gastrointestinal dysfunction is a disorder often found in critically ill patients that leads to nutritional deficiency resulting in the increase of the number of adverse events during hospitalization, more frequent hospital readmissions and steady quality of life deterioration after the discharge. The use of prokinetic agents plays an important pathogenetically substantiated role in treatment of intestinal failure syndrome. Drugs affecting the serotonin system can be considered as a promising group of prokinetic agents. Aim. To confirm the hypothesis that serotonin adipate has therapeutic potential for correction of adynamic gastrointestinal motility disorders with nutritional deficiency and is superior in efficiency to standard prokinetic therapy that includes metoclopramide and erythromycin. Methods. The patients, who met the inclusion criteria, were divided into two groups during the study. The index group received 30 mg serotonin adipate 3 times a day, if ineffective, the dose was increased to 40 mg 3 times a day, then on day 3 to 50 mg per day (the maximum daily dose was 150 mg). The control group received 10 mg metoclopramide 3 times a day and 200 mg erythromycin 6 times a day. Therapy was carried out for 10 days; treatment was terminated in case of beneficial outcome or side effects. The duration of prokinetic therapy was assessed, and the ultimate goal was gastrointestinal paresis resolution. The other endpoints were represented by the length of stay in the hospital and in the ICU, the duration of mechanical ventilation and vasopressor support. Results. The duration of prokinetic treatment in the index group was significantly lower (р<0.0001): 3 (2-3) days. The effects on the duration of vasopressor support have been also reported. It was lower in the index group, than in controls: 4 (3.0-7.0) days (р=0.078). Significance of the synthetic serotonin analogue (serotonin adipate) effects on the duration of mechanical ventilation, the length of stay in ICU and in the hospital, will be thoroughly investigated and reported in upcoming articles. No global side effects have been reported in the serotonin group. Conclusion. It has been shown that serotonin adipate has high therapeutic potential for correction of adynamic gastrointestinal motility disorders in non-surgical ICU patients with nutritional deficiency. Thus, serotonin adipate having an acceptable safety profile can be superior in efficiency to standard prokinetic therapy. The larger studies are required to confirm and generalize our findings.